Associations of Knowledge, Attitude, and Practices toward Anemia with Anemia Prevalence and Height-for-Age Z-Score among Indonesian Adolescent Girls. Issue 1 (June 2021) - Agustina, Rina; Wirawan, Fadila; Sadariskar, Arini A.; Setianingsing, Ainanur A.; Nadiya, Khairun; Prafiantini, Erfi; Asri, Eriana K.; Purwanti, Tutut S.; Kusyuniati, Sri; Karyadi, Elvina; Raut, Manoj K.
Background: Crucial gaps persist in knowledge, attitude, and practice (KAP) of adolescent girls that affect anemia and linear growth failure. Objective: To understand the role of KAP as a risk factor of anemia and linear growth problem in adolescent girls. Methods: We conducted a cross-sectional survey of 335 adolescent girls selected by clustered random sampling. The KAP questionnaire had 18 variables consisting of 9 knowledge, 3 attitude, and 6 practice components. Twelve variables addressed nutrition, dietary diversity, and health environments related to both anemia and stunting. The questionnaire was adapted from the 2014 Food and Agriculture Organization nutrition-related KAP guidelines for anemia. Dietary practice was evaluated from 2-day 24-hour recalls and a semi-quantitative food-frequency questionnaire. Associations between KAP and anemia, and height-for-age z -score (HAZ), were analyzed using multivariate logistic and linear regression models, respectively. Results: The mean hemoglobin (Hb) level was 119.7 g/L, with 44% of the adolescent girls being anemic (Hb < 120 g/L) and mean height was 151.0 cm with 25% being stunted (HAZ < −2 standard deviation [SD]). The median KAP score was 7 and ranged from 3 to 10. Low to moderate KAP scores were not significantly associated with being anemic (adjusted odds ratio [AOR] = 1.26; P = .43), however 1-point KAP score increment was associated with an increase of HAZ by 0.037 SD ( P = .012). Conclusions: The KAP related to diet and healthy environments was not associated with anemia prevalence, but was positively associated with increased HAZ among adolescent girls. Strategy to reduce anemia risk in this population should combine KAP improvement with other known effective nutrition interventions.